1982
DOI: 10.1144/gsl.qjeg.1982.015.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shrinkage cracks on pore-water pressures within a clay embankment

Abstract: For slope stability estimations, the soil pore-water conditions need to be accurately specified. The influence of cracks in clay was previously observed significantly to modify soil water response. In this study shrinkage cracks were monitored in a clay embankment where the soil water response to precipitation had been shown to be more rapid than the clay micro-permeability would predict. The cracks were shown to increase the hydraulic conductivity of the clay at all times of the year and to be the cause of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…On the favourable side, some of these soils have higher water retention capacity. In non-agricultural use, shrink-swell behaviour results in significant damage to lightly loaded structures and roadways and enhances the probability of shallow slope failures (Anderson et al, 1982). In the United States, total damage due to shrink-swell is estimated to cost from 6 to 11 billion dollars per year (Nuhfer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…On the favourable side, some of these soils have higher water retention capacity. In non-agricultural use, shrink-swell behaviour results in significant damage to lightly loaded structures and roadways and enhances the probability of shallow slope failures (Anderson et al, 1982). In the United States, total damage due to shrink-swell is estimated to cost from 6 to 11 billion dollars per year (Nuhfer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al, 1982;Anderson & Kneale, 1980a;Garrett & Wale, 1985;Birch & Dewar, 2002;Ridley et al, 2004;Briggs et al, 2013a).…”
Section: The Research Methods Used To Understand Embankment Failurementioning
confidence: 99%
“…However cracks in the road surface and damaged drainage may lead to water concentration and the development of positive pore water pressures (Anderson & Kneale, 1980b;Perry et al, 2003). Anderson et al, (1982) showed that the formation of shrinkage cracks during the summer months can facilitate rapid water entry during subsequent wet weather. This allowed positive pore water pressures to develop at shallow depth and trigger a shallow failure immediately adjacent to an instrumented highway slope (Anderson & Kneale, 1980a).…”
Section: Pore Water Pressure Induced Failure Of Highway and Railway Ementioning
confidence: 99%
“…This represents the greater permeability of surface soil due to desiccation cracking and fissuring, which facilitates rainfall infiltration (Anderson et al, 1982;Li et al, 2011, andGlendinning et al, 2014, showed that the vertical hydraulic conductivity of a compacted clay fill slope can be up to two orders of magnitude greater at about 0.1 m depth than at 1.0 m depth). Supplementary analysis showed that pore water pressures calculated in the model were insensitive to a similar increase in horizontal conductivity applied to the clay surface.…”
Section: Materials Propertiesmentioning
confidence: 99%